Using metacommunity ecology to understand environmental metabolomes - Robert E. Danczak (Nature Portfolio, 2020)
Despite growing interest in environmental metabolomics, we lack conceptual frameworks for considering how metabolites vary across space and time in ecological systems. Here, the authors apply (species) community assembly concepts to metabolomics data, offering a way forward in understanding the assembly of metabolite assemblages.